Stereoselective Csp(3)−Csp(2) Cross‐Couplings of Chiral Secondary Alkylzinc Reagents with Alkenyl and Aryl Halides - Skotnitzki, Juri (Angew Chem Int Ed Engl, 2019)
We report palladium‐catalyzed cross‐coupling reactions of chiral secondary non‐stabilized dialkylzinc reagents, prepared from readily available chiral secondary alkyl iodides, with alkenyl and aryl halides. This method provides α‐chiral alkenes and arenes with very high retention of configuration (dr up to 98:2) and satisfactory overall yields (up to 76 % for 3 reaction steps). The configurational stability of these chiral non‐stabilized dialkylzinc reagents was determined and exceeded several hours at 25 °C. DFT calculations were performed to rationalize the stereoretention during the catalytic cycle. Furthermore, the cross‐coupling reaction was applied in an efficient total synthesis of the sesquiterpenes (S)‐ and (R)‐curcumene with control of the absolute stereochemistry.